Islamic ethics and modern biotechnology - Latifah Amin,; Siti Fairuz Sujak,; Abdul Latif Samian,; Mohamad Sabri Haron,; Mohamad Nasran Mohamad,; Mohd Yusof Othman, (Universiti Kebangsaan Malaysia, 2009)
Contribution of modern biotechnology to the betterment of the agricultural sector and human health is undeniable. However, many consumers, environmental groups and some scientists have voiced strong concerns over the long term effects of modern biotechnology products on human health and environment. According to some researchers, the central problem underlying biotechnology is not just its short term benefits and long term drawbacks, but the overall attempt to “control” living nature on an erroneous mechanistic view. We as human have conscience and our religious belief. Many religions do not allow unrestricted interference with life such as genetic engineering. The pace of discovery in genetic based biotechnology is very rapid and there is anxiety that a kind of technological compulsion (if we can do it, let’s do it) will drive development ahead of proper ethical consideration of their propriety. In Islam, ethic is known as akhlaq based on al-Qur’an and al-Hadith. Ethic of modern biotechnology is classified according to three part of akhlaq: ethical issues related to God (Allah), ethic among human beings and ethic related to living things. In this paper, ethical aspects of modern biotechnology will be discussed from Islamic perspective